A New Design of the Intelligent Sign Language Interpreters - Waraporn Nacharee; Suriya Pradisathaporn; Somkuan Kaviya; Nataya Nakasan; Preecha P. Yupapin (My University, 2011)
According to the declaration of human rights (UN) and the constitution B.E. 2540 of the Kingdom of Thailand and the present constitution, the disabled in hearing have the rights to study in the educational institutes of general persons. When the disabled in hearing study in higher levels, they find the problems of the sign language interpreters and other facilities, which affect their education. So several agencies and educational institutes try to solve these problems by inventing the Thai sign language interpreter machine and Dinsow robot, which the intelligent robot can interpret the sign languages into words. But nobody has developed the smaller communicative machine which can take with oneself and communicate two ways. In this paper, the concept of the new intelligent sign language interpreters has been developed with only two pieces of equipments, that composes of the braintooth and the mobile reader work together to communicate between teacher with learners.
Keywords: nobody; Declaration; Hand Gesture Recognition Systems